Indoor navigation system using Dijkstra's algorithm for emergency situation / Mohd Faizulhayad Mashuri - Mashuri, Mohd Faizulhayad (2015)
This research discuss on an implementation of route planning in Indoor Navigation System (INS) for emergency situation. Global Positioning System (GPS) cannot be used for INS since signals sent by satellites cannot penetrate the construction materials inside a building. Wireless Fidelity (Wi-Fi) is the system that can make INS possible. By implementing Radio Signal Strength (RSS) provided by Wireless Fidelity (Wi-Fi), Reference Points (RP)s with it designated RSS can be setup across the area desired. The connection or paths between each RP can be created to create the best route to the destination. The algorithm used for this route planning is Dijkstra's algorithm. The result of this technique shows higher accuracy in terms of shortest distance taken to the destination compared to other technique and the implementation of this technique are easy since users only have to manipulate the weight between each RPs according to obstacle that exist along the paths. Bigger obstacles will gives higher value of weight. Dijkstra's algorithm can provide shortest route to be used by user in a fast manner due to its medium algorithm complexity compared to the other two (2) algorithms. Dijkstra's algorithm also proved that this algorithm has the capability to provide alternative route in case of unpredicted existence of obstacles along the main route. Thus, it can be conclude that Dijkstra's algorithm is the best algorithm to be used for route planning compared to Bellman-Ford and A* algorithm.